How Not to Do a Mindset Intervention: Learning from a Mindset Intervention among Students with Good Grades - Orosz, Gábor; Péter-Szarka, Szilvia; Bőthe, Beáta; Tóth-Király, István; Berger, Rony (Frontiers in Psychology, 2017)
The present study examined the effectiveness of a Growth Mindset intervention based on Dweck et al.’s (1995) theory in the Hungarian educational context. A cluster randomized controlled trial classroom experiment was carried out within the framework of a train-the-trainer intervention among 55 Hungarian 10th grade students with high Grade Point Average (GPA). The results suggest that students’ IQ and personality mindset beliefs were more incremental in the intervention group than in the control group three weeks after the intervention. Furthermore, compared to both the baseline measure and the control group, students’ amotivation decreased. However, no intrinsic and extrinsic motivation change was found. Students with low grit scores reported lower amotivation following the intervention. However, in the second follow-up measurement—the end of the semester— all positive changes disappeared; and students’ GPA did not change compared to the previous semester. These results show that mindset beliefs are temporarily malleable and in given circumstances, they can change back to their pre-intervention state. The potential explanation is discussed in the light of previous mindset intervention studies and recent findings on wise social psychological interventions.